Surgical Morbidity and Mortality From the Multicenter Randomized Controlled NeoRes II Trial: Standard Versus Prolonged Time to Surgery After Neoadjuvant Chemoradiotherapy for Esophageal Cancer. Issue 5 (November 2020) - Nilsson, Klara; Klevebro, Fredrik; Rouvelas, Ioannis; Lindblad, Mats; Szabo, Eva; Halldestam, Ingvar; Smedh, Ulrika; Wallner, Bengt; Johansson, Jan; Johnsen, Gjermund; Aahlin, Eirik Kjus; Johannessen, Hans-Olaf; et al.
Abstract : Objective: To investigate if prolonged TTS after completed nCRT improves postoperative outcomes for esophageal and esophagogastric junction cancer. Summary of Background Data: TTS has traditionally been 4–6 weeks after completed nCRT. However, the optimal timing is not known. Methods: A multicenter clinical trial was performed with randomized allocation of TTS of 4–6 or 10–12 weeks. The primary endpoint of this sub-study was overall postoperative complications defined as Clavien-Dindo grade II-V. Secondary endpoints included complication severity according to Clavien-Dindo grade IIIb-V, postoperative 90-day mortality, and length of hospital stay. The study was registered in Clinicaltrials.gov (NCT02415101). Results: In total 249 patients were randomized. There were no significant differences between standard TTS and prolonged TTS with regard to overall incidence of complications Clavien-Dindo grade II–V (63.2% vs 72.6%, P = 0.134) or regarding Clavien-Dindo grade IIIb–V complications (31.6% vs 34.9%, P = 0.603). There were no statistically significant differences between standard and prolonged TTS regarding anastomotic leak ( P = 0.596), conduit necrosis ( P = 0.524), chyle leak ( P = 0.427), pneumonia ( P = 0.548), and respiratory failure ( P = 0.723). In the standard TTS arm 5 patients (4.3%) died within 90 days of surgery, compared to 4 patients (3.8%) in the prolonged TTS arm ( P = 1.0). Median length of hospital stay was 15 days in the standard TTS arm and 17 days in the prolonged TTS arm ( P = 0.234). Conclusion: The timing of surgery after completed nCRT for carcinoma of the esophagus or esophagogastric junction, is not of major importance with regard to short-term postoperative outcomes. Abstract : Supplemental Digital Content is available in the text